Tipe Masker pada Murid Sekolah Dasar selama Pertemuan Tatap Muka Terbatas di Masa Pandemi COVID-19 - Adelina, Rosa; Fajra, Jenisha Rani; Putri, Annisya Ayu; Zaafira, Reyhan Diva (Jurnal Ilmiah Medicamento, 2024)
In March 2020, the World Health Organization declared COVID-19 a pandemic. As a result, elementary school learning was primarily conducted online. However, in January 2022, the Government of Indonesia announced that limited face-to-face meetings in schools could be conducted due to the vaccination of elementary school students. Nevertheless, these meetings are still subject to health protocols, including wearing masks. This study aims to examine the types and brands of masks used, as well as elementary school students' knowledge regarding the layers of masks and sources of information on mask usage during limited face-to-face meetings. The research utilized a descriptive method and cross-sectional study design. The sample was obtained through purposive sampling of elementary school students in the Jabodetabek area, with a total of 408 students included in the study. Univariate data analysis was performed using SPSS 25 to describe the observed results. The findings indicate that the three most used types of masks were duckbill masks (33%), medical masks (25%), and KF94 masks (21%). The two highest response groups reported that 41.4% of respondents believed the masks to consist of only one layer, while the other 35% believed they consisted of three layers. The most used mask brands are those produced in China. Teachers and parents are the primary sources of knowledge regarding the use of masks among elementary school students. According to the study's findings, there is a strong correlation between the information received and the use of masks by these students.